The effect of discovery learning model on learning outcomes of IPAS class IV elementary school - Maran, Maria Antonia Oke; Puang, Desi Maria El; Hero, Hermus (Institute of Computer Science (IOCS), 2025)
A recent study of fourth grade students at SDK Nita 1 revealed that a subset of students exhibited challenges in comprehending and applying the material, resulting in diminished student learning outcomes. This phenomenon can be attributed to the instructional approach employed by the teacher, who primarily relied on the textbook as a primary source of instruction and assessment, with minimal engagement in discussion activities. The efficacy of this instructional method was further underscored by the findings of a daily test, which indicated that 19 out of 27 students demonstrated inadequate mastery of the material. Of these 19 students, some were able to answer questions from the teacher, but only after reading the material in the book. Others demonstrated an inability to answer even though they had read the material in the book. To address this issue, the discovery learning model was employed. The research design utilized a one-group pretest-posttest design, with a sample size of 27. The collection of data was achieved through the administration of tests and observations, with research instruments in the form of test questions and observation sheets. The analysis of data involved the implementation of normality tests using the Kolmogorov-Smirnov test and hypothesis testing through the utilization of t-tests. The findings of the study yielded a significant value (2 tailed) > 0.05, thereby supporting the acceptance of the null hypothesis (Ha) and rejecting the alternative hypothesis (Ho). The conclusion of the study asserts the presence of an effect on learning outcomes of fourth grade students of SDK Nita 1 due to the implementation of the discovery learning model.